Tetrabutylammonium iodide - J. Tomkinson, ISIS Facility (My University, 2017)
Inelastic Neutron Scattering spectrum of Tetrabutylammonium iodide, [CH₃(CH₂)₃]₄, measured on the TFXA instrument.
Keywords: TFXA